2016
DOI: 10.1002/prca.201500120
|View full text |Cite
|
Sign up to set email alerts
|

2D‐DIGE‐based proteomic analysis of intracoronary versus peripheral arterial blood platelets from acute myocardial infarction patients: Upregulation of platelet activation biomarkers at the culprit site

Abstract: Purpose: Platelets play a fundamental role in the atherothrombotic events that lead to an acute myocardial infarction. In the present study we compared the proteome of intracoronary and peripheral arterial platelets from ST-elevation myocardial infarction (STEMI) patients in the search for potential platelet biomarkers/drug targets related to what is happening at the culprit site. Experimental design: Ten STEMI patients were recruited and blood collected from the occluded coronary artery, at the culprit site, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…There are precedents of intracoronary studies, using a similar approach, that allowed the detection of platelet activation biomarkers in the intracoronary blood. Indeed, we recently showed an up-regulation of signaling proteins in platelets from intracoronary blood at the culprit site - in comparison with peripheral platelets - in STEMI patients25, which highlights the relevance of studying platelets from occluded blood in direct contact with the thrombus as activation biomarkers are more prompted to be elevated in these platelets. As another example, Gresele and colleagues recently showed that platelets release matrix metealloproteinase-2 in the coronary circulation of patients with ACS as a consequence of platelet activation26.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There are precedents of intracoronary studies, using a similar approach, that allowed the detection of platelet activation biomarkers in the intracoronary blood. Indeed, we recently showed an up-regulation of signaling proteins in platelets from intracoronary blood at the culprit site - in comparison with peripheral platelets - in STEMI patients25, which highlights the relevance of studying platelets from occluded blood in direct contact with the thrombus as activation biomarkers are more prompted to be elevated in these platelets. As another example, Gresele and colleagues recently showed that platelets release matrix metealloproteinase-2 in the coronary circulation of patients with ACS as a consequence of platelet activation26.…”
Section: Discussionmentioning
confidence: 92%
“…Intracoronary samples from STEMI patients were taken during normal hemodynamics procedure using a Pronto V3 catheter (Vascular Solutions), which occludes antegrade flow allowing collecting culprit site blood from the distal artery252728. Peripheral arterial samples were obtained from the radial artery through which the sheath was inserted.…”
Section: Methodsmentioning
confidence: 99%
“…showing that these proteins had more than two-fold increase in their expression profiles in the "thrombinactivated" vs "resting" platelets. We recovered a high overlap of proteins members with the kinome family reported already by other proteomic analyses, [20][21][22][23][24][25][26][27][28][29][30] that are also indexed in many other research studies related to the proteomic profiling of agonists activated platelets, such as the "Adhesome" and "Platelet Web" databases, as described later in the results section. Other major pathways predicted by IPA to be up-regulated in the proteome of "thrombin-activated platelets" were mapped to the cytoskeleton, actin and RhoA mediated cellular signaling ( Figure 18).…”
Section: Figure 14mentioning
confidence: 88%
“…The "in solution" digestion with three enzymes (trypsin/LysC/Glu-C), enabled the extraction of peptides from the total platelet proteome, including the membrane-derived and microvesicles contained in the releasates, as reported previously by other studies on platelets proteomics. [20][21][22][23][24][25][26][27][28][29][30] The extracted peptides were subjected to nano LC/MS/MS sequencing on a Q Exactive quadrupole orbitrap mass spectrometer, as summarized in the protocol shown in Figure 1. The label-free proteomics analysis employed the label free quantification (LFQ) module provided by PEAKS 8.5 (Bioinformatics Solutions Inc.), In addition, the changes in the protein expression profiles were complemented by an additional analysis involving the Scaffold and per SPECtives software (Proteome Software Inc.).…”
Section: Development Of a Workflow For Implementing The Label-free Phmentioning
confidence: 99%
See 1 more Smart Citation